Histone 3 Methyltransferases Alter Melanoma Initiation and Progression Through Discrete Mechanisms - DiNapoli, Sara E.; Martinez-McFaline, Raúl; Shen, Hao; Doane, Ashley S.; Perez, Alexendar R.; Verma, Akanksha; Simon, Amanda; Nelson, Isabel; Balgobin, Courtney A.; Bourque, Caitlin T.; Yao, Jun; Raman, Renuka; et al. (Frontiers in Cell and Developmental Biology, 2022)
Perturbations to the epigenome are known drivers of tumorigenesis. In melanoma, alterations in histone methyltransferases that catalyze methylation at histone 3 lysine 9 and histone 3 lysine 27—two sites of critical post-translational modification—have been reported. To study the function of these methyltransferases in melanoma, we engineered melanocytes to express histone 3 lysine-to-methionine mutations at lysine 9 and lysine 27, which are known to inhibit the activity of histone methyltransferases, in a zebrafish melanoma model. Using this system, we found that loss of histone 3 lysine 9 methylation dramatically suppressed melanoma formation and that inhibition of histone 3 lysine 9 methyltransferases in human melanoma cells increased innate immune response signatures. In contrast, loss of histone 3 lysine 27 methylation significantly accelerated melanoma formation. We identified FOXD1 as a top target of PRC2 that is silenced in melanocytes and found that aberrant overexpression of FOXD1 accelerated melanoma onset. Collectively, these data demonstrate how histone 3 lysine-to-methionine mutations can be used to uncover critical roles for methyltransferases.